2020
DOI: 10.3390/molecules25040865
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Improves Exercise Endurance by Promoting Mitochondrial Biogenesis and Myoblast Differentiation

Abstract: Red ginseng has been reported to elicit various therapeutic effects relevant to cancer, diabetes, neurodegenerative diseases, and inflammatory diseases. However, the effect of red ginseng on exercise endurance and skeletal muscle function remains unclear. Herein, we sought to investigate whether red ginseng could affect exercise endurance and examined its molecular mechanism. Mice were fed with red ginseng extract (RG) and undertook swimming exercises to determine the time to exhaustion. Animals fed with RG ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Among these parameters, spare capacity has been considered as a crucial parameter of bioenergetic profile in cells that are corresponding to the supply of substrate during increased demand for energy consumption. Here, ginsenoside Rd, Re and Rg 1 showed enhancement of spare capacity and ATP formation under the insult of applied Aβ: this observation was consistent with an increase of pathway related to energy production after treatment of ginseng extract [ 31 ]. Amongst these ginsenosides, Rg 1 displayed the best protective effects on the culture under Aβ-induced mitochondrial toxicity.…”
Section: Discussionsupporting
confidence: 66%
“…Among these parameters, spare capacity has been considered as a crucial parameter of bioenergetic profile in cells that are corresponding to the supply of substrate during increased demand for energy consumption. Here, ginsenoside Rd, Re and Rg 1 showed enhancement of spare capacity and ATP formation under the insult of applied Aβ: this observation was consistent with an increase of pathway related to energy production after treatment of ginseng extract [ 31 ]. Amongst these ginsenosides, Rg 1 displayed the best protective effects on the culture under Aβ-induced mitochondrial toxicity.…”
Section: Discussionsupporting
confidence: 66%
“…To evaluate the influence of the CMEE on exercise, we employed the grip strength test model and used the red ginseng as positive control. The red ginseng is one of the most famous medicinal herb and has been reported to the various health beneficial effects including the protection of muscle damage, the relief of fatigue, and the improvement of exercise endurance [ 15 ]. There were no significant changes in body weight during the experiment ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, in this study, KRG was shown to increase the mtDNA copy number more than the placebo. A previous study showed that KRG improved exercise performance, increased the ATP production capacity of muscle cells, and stimulated myoblast differentiation in mice [ 17 ]. An animal study showed that the mtDNA copy number and messenger RNA expression levels of mitochondrial biogenesis-related transcription factors increased more in those with diabetes who took KRG than those who took a placebo [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kim et al reported that the Rg3 component in KRG increased the expression of PGC-1α, NRF-1, and TFAM in an in vitro model [ 22 ]. Additionally, Shin et al showed that KRG improved swimming performance in mice and enhanced TFAM and NRF-1 gene expression levels [ 17 ]. Therefore, KRG may lead to improvements in the PGC-1α-NRF1-TFAM pathway, which contributes to the increased mtDNA copy number.…”
Section: Discussionmentioning
confidence: 99%